Coupled Dynamics of a Rotor-Journal Bearing System Equipped with Thrust Bearings - Yu Lie; R.B. Bhat (Shock and Vibration)
The rotordynamic coefficients of fixed-pad thrust bearing are introduced and calculated by using the out-domain method, and a general analysis method is developed to investigate the coupled dynamics of a rotor equipped with journal and thrust bearings simultaneously. Considerations include the effects of static tilt parameters of the rotor on rotordynamic coefficients of thrust bearing and the action of thrust bearing on system dynamics. It is shown that thrust bearing changes the load distribution of journal bearings and the static deflection of the rotor and delays the instability of the system considerably in lateral shaft vibration.